Behavior of Peruvian carrot (Arracacia xanthorrhiza) and cassava (Manihot esculenta) starches subjected to the heat-moisture treatment - Moraes, Jaqueline de [UNESP]; Branzani, Rafaela S. [UNESP]; Franco, Celia Maria Landi [UNESP] (My University, 2014)
Peruvian carrot and cassava starches were isolated, adjusted to 30 and 35% moisture, and heatedat 90°C for 8 h. Structural and physicochemical characteristics of the treated starches wereevaluated and compared. High performance anion exchange chromatography with pulsedamperometric detector (HPAEC-PAD), gel permeation chromatography (GPC), and amylosecontent, revealed that the HMT did not change the chemical structures of the starches. A largeagglomeration of granules was observed from SEM, particularly in the Peruvian carrot starch.Crystalline patterns in Peruvian carrot and cassava starches changed from B to C and CAto A,respectively. Relative crystallinity decreased from 30 to 25% in Peruvian Carrot starch, andincreased from 35 to 37% in cassava starch adjusted to 30% moisture. SF and peak viscositydecreased, breakdown was almost completely eliminated (particularly in the Peruvian carrotstarch), and ﬁnal viscosity increased. WAI and WSI increased as moisture levels of bothstarches increased. Gelatinization temperatures increased and enthalpy decreased. Degrees ofgelatinization increased as the moisture level increased, reaching 33 and 72% in the cassavaand Peruvian carrot starches, respectively. HMT strengthened the intra- and intermolecularinteractions of starches and increased their stability during heating and shearing, but also causeda partial gelatinization in the starches, particularly in Peruvian carrot starch.
Keywords: heat-moisture; physico-chemical properties; Structure